Exploring the Human Element: A Qualitative Study of the Use of Human Resources Accounting in an Organizational Context - Tanjung, Amries Rusli; Komardi, Dadi; Renaldo, Nicholas; Reilly, William; Yu, Hou (First Ciera Publisher, 2023)
This qualitative research explores the impact of Human Resources Accounting (HRA) on organizational dynamics, recognizing human capital as crucial for sustained success. Titled